Use of sport science by Olympic athletes for medal performance in Rio 2016 - Wilber, R. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Team USA has produced relatively strong performance results in the Olympic Games since the inception of the modern Olympics in 1896. Team USA is comprised of several national governing bodies (NGBs), which provide both the administrative structure and performancesupport structure for elite athletes and coaches within that particular NGB, or sport. USA Swimming and USA Track & Field are historically the two most successful NGBs in Olympic sport for Team USA. These two NGBs alone have consistently won approximately 60 percent of the total medals won by Team USA at any given Olympic Games, and this trend is expected to continue at the RIO 2016 Olympics. The overall strategy of USA Swimming and USA Track & Field in preparation for RIO 2016 is to "defend" medals in traditionally successful events, and to "go on offense" in events where returning Team USA athletes placed 4th through 8th in LONDON 2012, or in events that are relatively new (e.g., 10km swimming). This presentation will focus on select Olympic athletes from USA Swimming and USA Track & Field, and their implementation of various components of sport science in preparation for Rio 2016. Highlighted within this presentation will be examples of specific "Olympic performance initiatives" utilized over the past four years with medal-potential athletes from USA Swimming and USA Track & Field.